EKOWISATA RAMMANG-RAMMANG SEBAGAI LABORATORIUM PEMBELAJARAN KONTEKSTUAL GEOGRAFI DI KABUPATEN MAROS - Ikhsan, Muhammad; Haris, Haris (JAMBURA GEO EDUCATION JOURNAL, 2022)
This study aims to identify objects or locations in the Ecotourism area of Rammang-Ramang Maros which can be used as a Geography Contextual Learning Laboratory). This type of research is descriptive qualitative research, which means that this research identifies and describes every object in the Rammang-Rammang Ecotourism location that can be studied using a geography approach, then mapped into a geography learning laboratory concept. This research utilizes primary data (observation) and secondary data (library study). The data collected, both primary and secondary, were processed, analyzed, and then mapped into geographic laboratory locations for students to use in contextual geography learning. The results showed that there were 6 (six) location points that could be used as a geography laboratory in the Rammang-Rammang ecotourism area. Each location describes a typical geographic study object from the aspects of hydrology, geology, geomorphology, and biodiversity. The six location points that have been plotted as a geography laboratory are Batu Forest (Tower Karts), Berua Village, Tunnel Cave, Berlian Cave, Bat Cave, and Bidadari Lake. The location is made as a geography learning laboratory because the six locations have geosphere phenomena that are relevant to some of the achievements of geography learning in the independent learning curriculum. So, this research has produced a geography laboratory that conceptually makes it easier for teachers and students to study contextual-based geography with the concept of outdoor study learning such as field trips or field studies.